Dorian Gray of the Suburbs: Eternal Youth and (Un)successful Aging in John Cheever’s Fictions - Alicja Piechucka (European Journal of American Studies)
The aim of the article is to explore the pursuit of eternal youth as depicted in John Cheever’s selected fictions. Cheever’s “O Youth and Beauty!” and “The Swimmer” feature middle-aged and middle-class protagonists living in the American suburbs. Tormented by a longing for their lost youth, attractiveness, fitness, joie de vivre and something more elusive they cannot identify, Cheever’s characters embark on grotesque and hyperbolic as well as desperate and inevitably futile attempts to tame time by achieving backbreaking athletic feats. In doing so, they exemplify the Dorian Gray syndrome, immaturity and narcissism. Importantly, they also reveal their existential drama, at once modern and ageless. In my essay, I propose to close-read the two stories in light of the theories of DSG and thought surrounding the contemporary anti-aging movement, with particular focus on the concept of successful aging. My argument is that the characters’ obsession with remaining—preferably forever—young, keeping their good looks and staying fit pushes them toward objectification, self-objectification and a path of self-destruction, and inscribes itself in the capitalist and individualist paradigm.